2021
DOI: 10.1615/plasmamed.2021038035
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Influence of Helium and Argon Plasma on Crystallogenic Properties of the Blood

Abstract: The aim of this study was to compare the biological effects of helium and argon plasma in vitro. The cold plasma was generated using a device developed at the Institute of Applied Physics of the Russian Academy of Sciences (Nizhny Novgorod), which uses the principle of microwave ionization of the gas flow. We studied the crystallogenic activity of blood plasma. The description of dehydrated blood plasma samples was performed morphologically, using a system of visuametric parameters. Main morphometric parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Cold plasma generation was performed using a device of an original design using the principle of microwave ionization of a gas stream [25,26]. The gas supply rate was strictly controlled for all procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Cold plasma generation was performed using a device of an original design using the principle of microwave ionization of a gas stream [25,26]. The gas supply rate was strictly controlled for all procedures.…”
Section: Methodsmentioning
confidence: 99%
“…A separate issue is the clarification of the role of the carrier gas in the implementation and features of the action of cold plasma on biological objects. To solve this problem, we compared the modification of the physicochemical properties of blood plasma during its treatment with helium and argon plasma [ 64 ]. It was found that the use of helium as a carrier gas provides a more physiological response of the biosystem, contributing to the optimization of the crystalloscopic picture of the biological fluid.…”
Section: The Authors’ Own Research In the Field Of Studying Local And...mentioning
confidence: 99%